FINANCIAL SOCIALIZATION AMONG GENERATION Z: HOW CHILDREN OF MILLENNIAL PARENTS INTERNALIZE MONEY VALUES - Taufiq Hidayat; Wahjoedi Wahjoedi; Hari Wahyono; Sugeng Hadi Utomo (JURNAL EDUSCIENCE, 2026)
Purpose – This study aims to explore how Generation Z in East Java interprets and internalises financial values transmitted by millennial parents amid the dominance of digital technology and social media. Specifically, it examines how family financial teachings are renegotiated in the context of digital algorithms, peers, and contemporary consumer culture.Methodology – A qualitative phenomenological approach was employed to explore Gen Z's lived experiences of financial socialization. Data were gathered through semi-structured interviews with 25 Gen Z individuals and several millennial parents. Interpretative Phenomenological Analysis (IPA) was used to generate themes and interpret meaning-making processes across cases.Findings – Four primary themes were discerned: (1) parental modeling, wherein daily financial routines cultivated prudence and budgeting skills; (2) financial conversations, characterized by dialogic negotiation that promoted reasoning and deferred gratification; (3) digital finance negotiation, where participants integrated parental norms with fintech practices, resulting in hybrid financial values; and (4) identity and social comparison, illustrating the tensions between familial values and social media-induced lifestyle pressures.Contribution – Financial value internalization among Indonesian Gen Z is both intergenerational and sociotechnical. The findings point out the need for financial education that integrates digital literacy, awareness of algorithmic influence, and strategies to manage social comparison pressures.